Medical Costs of Evaluating Intellectual and Developmental Disabilities in a Unit Established in a Japanese Outpatient Office - Horiguchi, Toshihiro; Akiyama, Chieko (Journal of Intellectual Disability - Diagnosis and Treatment, 2016)
To determine the average medical cost incurred for early identification of intellectual and developmental disabilities in children, we retrieved the records of 264 children who had visited our consulting unit from 2005 until the end of March 2012. In the evaluation process, each child took psychological assessments and the parents were provided with solutions to enable the children to overcome their delay in school. As a whole, while the average number of visits did not differ by the diagnosis, the average medical cost differed by the diagnosis. The consultation unit was effective for gradually diminishing the medical costs incurred. Our in-clinic consultation system proved useful for early identification of intellectual and developmental disabilities in children and minimization of the medical costs incurred for the process.